AB0557 Haematological involvement (CYTOPENIA) at the time of the diagnosis is associated with less severe ocular involvement in patients with primary sjogren syndrome. (12th June 2018) - Buzatu, C.G.; Daia-Iliescu, S.; Saulescu, I.; Zaharia, D.; Purice, C.; Gudu, T.; Borangiu, A.; Groseanu, L.; Bojinca, V.; Berghea, F.; Balanescu, A.; Predeteanu, D.; et al.
Abstract : Background: In patients with primary Sjogren Syndrome (pSS), haematological involvement – autoimmune cytopenia, might be present at the time of the diagnosis or can develop in time after the characteristic glandular involvement. (1, 2) Objectives: The objective of the study is to evaluate the correlation between glandular involvement (ocular) and presence of cytopenia in patients diagnosed with pSS. Methods: A retrospective analysis was performed on a cohort of patients diagnosed with primary Sjogren Syndrome under surveillance in one Rheumatology Centre between 2009 and 2016. The documented cases have been diagnosed according to the 2002 American-European Consensus group classification criteria, the 2012 ACR criteria or 2016 ACR/EULAR Classification Criteria for pSS. The EULAR Sjogren's Syndrome Disease Activity Index (ESSDAI) was calculated for all patients. Ocular assessment and follow-up were performed in collaboration with the same ophthalmologist. The data was analysed using Windows Excel/SPSS20.0. Results: 30 female patients diagnosed with pSS were included in the study. The mean age at the time of diagnosis was 52.1 years±SD 9.1. The ESSDAI was calculated for all patients at baseline: 5 (17%) patients presented high disease activity (ESSDAI >14), 14 (46%) patients moderate disease activity (5≤ESSDAI≤13) and 11 (37%) patients low disease activity (ESSDAI <5). The domain weight for glandular involvement when calculating ESSDAI is fairly low (2), 1 so in the studied group there wasn't obtained a statistically significant correlation between ocular involvement and disease activity as evaluated by ESSDAI. In the clinical case series, Spearman's rank correlation coefficient between haematological (autoimmune cytopenia), and biological markers (hypocomplementemia) and ocular involvement were calculated. A strong negative correlation was found between autoimmune cytopenia and glandular manifestations (ocular involvement-xerophthalmia) (r=-0, 60; p<0, 05). Another strong negative correlation was obtained between hypocomplementemia and severe ocular involvement (corneal ulceration) (r=-0, 59, p<0, 05), respectively. Conclusions: Patients diagnosed with primary Sjogren Syndrome that presented at disease's onset cytopenia and hypocomplementemia had a less severe ocular involvement. References: [1] Seror R, Theander E, Brun JG, et al, Validation of EULAR primary Sjögren's syndrome disease activity (ESSDAI) and patient indexes (ESSPRI)Annals of the Rheumatic Diseases 2015;74:859–866. [2] Shiboski CH, Shiboski SC, Seror R, Criswell LA, Labetoulle M, Lietman TM, Rasmussen A, Scofield H, Vitali C, Bowman SJ, Mariette X, International Sjögren's Syndrome Criteria Working Group, Ann Rheum Dis. 2017Jan;76(1):9–16. [3] Koh JH, Lee J, Chung SH, Kwok SK, Park SH, Relation of Autoimmune Cytopenia to Glandular and Systemic Manifestations in Primary Sjögren Syndrome: Analysis of 113 Korean Patients, J Rheumatol. 2015Oct;42(10):1817–24. Disclosure of Interest: None declared